2020
DOI: 10.3390/antiox9111035
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as a Natural Enhancer of Neuroplasticity—An Overview of the Mechanism of Neurorestorative Action

Abstract: Neuroplasticity is a complex physiological process occurring in the brain for its entire life. However, it is of particular importance in the case of central nervous system (CNS) disorders. Neurological recovery largely depends on the ability to reestablish the structural and functional organization of neurovascular networks, which must be pharmacologically supported. For this reason, new forms of therapy are constantly being sought. Including adjuvant therapies in standard treatment may support the enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 116 publications
0
40
0
Order By: Relevance
“…Flavonoids are polyphenolic compounds found in fruits and vegetables, and are highly effective scavengers of most oxidizing molecules, including singlet oxygen, and various free radicals implicated in several diseases including AD. Flavonoids can provide protection to the brain cells by modulating intracellular signals and promoting cellular survival [ 41 ]. In the current study highest contents of total phenolic (88.23 ± 1.13) and flavonoids (85.93 ± 0.67) were detected in Fa.EtAc followed by Fa.Chf extract (TPC: 75.12 ± 1.58 and TFC: 77.83 ± 2.16).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are polyphenolic compounds found in fruits and vegetables, and are highly effective scavengers of most oxidizing molecules, including singlet oxygen, and various free radicals implicated in several diseases including AD. Flavonoids can provide protection to the brain cells by modulating intracellular signals and promoting cellular survival [ 41 ]. In the current study highest contents of total phenolic (88.23 ± 1.13) and flavonoids (85.93 ± 0.67) were detected in Fa.EtAc followed by Fa.Chf extract (TPC: 75.12 ± 1.58 and TFC: 77.83 ± 2.16).…”
Section: Discussionmentioning
confidence: 99%
“…Related to these or other properties, flavonoid intakes have been associated with numerous health-promoting physiological benefits for cardiovascular disease, cancer, neurological disorders, aging, obesity, etc. [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For this reason, a wide range of human intervention studies has been developed, and the results offer promising applications in the prevention of several disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The most numerous group of polyphenols are flavonoids, which include flavanones, flavanols, flavones, isoflavones, flavonols, and anthocyanins, as well as biflavonoids, flavonolignans, prenylflavonoids, flavonoid glycosides, chalcones and proanthocyanins [ 47 ]. Several observational studies have shown that flavonoid-rich food consumption has a positive effect on improving cognitive function, regardless of age and medical history [ 48 , 49 , 50 , 51 ].…”
Section: Natural Compoundsmentioning
confidence: 99%
“…The antioxidant effect of flavonoids is based on scavenging free radicals, chelating metals, and silencing pro-oxidative enzymes (xanthine oxidase, protein kinase C—PKC, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, COX and lipoxygenase) [ 12 ]. The molecular neuroprotective mechanism of these compounds is often associated with the activation of the cAMP response element-binding protein (CREB)/brain-derived neurotrophic factor (BDNF)/tropomyosin-related kinase B receptor (TrkB)/phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) and/or ERK 1/2 pathways, therefore even small doses of these compounds can cause a synergistic effect [ 47 ]. One of the most abundant naturally occurring flavonoids is quercetin, contained, among others, in cabbage, spinach, blackcurrant, blueberry, thus in plants particularly recommended in the MIND diet, but it is also the active ingredient of many supplements.…”
Section: Natural Compoundsmentioning
confidence: 99%
See 1 more Smart Citation